Startup challenges in Florianópolis (SC): factors that lead entrepreneurs to failure - Leite, Eduardo Dias (2024)
Startup's contribution is recognized, despite a high risk strategy but high reward, with significant failure rate and a low success ratio. The purpose of this research is to analyze the factors that lead the individual not to succeed in creating startups located in the city of Florianópolis (SC). The methodology used is content analysis of 14 interviews and the tool used was the Python programming language. The analysis presented the results where they pointed out that the region's startups fail because there was a failure in long -term planning, did not adapt to market changes, problems between the partners, the lack of resources and the entrepreneurs did not take into account the real needs of Market, testing and adapting your project with the community and consequently, did not offer the appropriate product/service and support to the customer. Keywords: entrepreneurs; startups; startups in florianópolis; failure.